導言 中國生命倫理研究: 良好開端，大有可為 - FAN, Ruiping (International Journal of Chinese & Comparative Philosophy of Medicine, 2007)
LANGUAGE NOTE | Document text in Chinese 2007 年1 月9-10 日， 香港浸會大學應用倫理學研究中心成功舉辦了第一屆「建構中國生命倫理學」研討會， 與會學者們應邀從中國傳統倫理觀出發， 就當代社會面臨的一些重要道德問題展開了富有成效的討論。呈現在讀者面前的本期期刊， 就是由這屆研討會中的論文選編和修改以後組成的。 DOWNLOAD HISTORY | This article has been downloaded 34 times in Digital Commons before migrating into this platform.